2021
DOI: 10.3390/toxins13060424
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen Derivatives Alter Retromer-Dependent Endosomal Tubulation and Sorting to Block Retrograde Trafficking of Shiga Toxins

Abstract: Shiga toxin 1 and 2 (STx1 and STx2) undergo retrograde trafficking to reach the cytosol of cells where they target ribosomes. As retrograde trafficking is essential for disease, inhibiting STx1/STx2 trafficking is therapeutically promising. Recently, we discovered that the chemotherapeutic drug tamoxifen potently inhibits the trafficking of STx1/STx2 at the critical early endosome-to-Golgi step. We further reported that the activity of tamoxifen against STx1/STx2 is independent of its selective estrogen recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The importance of these chemical modulators of vesicular trafficking in deciphering the key steps of these pathways and toxin mechanisms of action perfectly illustrates the cross-feeding between the disciplines of cell biology and infectiology ( Forrester et al., 2020 ; Sandvig et al., 1991 ; Selyunin et al., 2021 ). Notably, these different compounds have been used as tools to discern the different physicochemical requirements of AB toxins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of these chemical modulators of vesicular trafficking in deciphering the key steps of these pathways and toxin mechanisms of action perfectly illustrates the cross-feeding between the disciplines of cell biology and infectiology ( Forrester et al., 2020 ; Sandvig et al., 1991 ; Selyunin et al., 2021 ). Notably, these different compounds have been used as tools to discern the different physicochemical requirements of AB toxins.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CNFy and CNF3 showed distinctive sensitivity to EGA but similar dose-response profiles to ABMA, indicating differential endosomal escape of the two highly homologous toxins ( Haywood et al., 2021 ). Similarly, tamoxifen was identified in a drug repurposing screen to block the fusion of late endosomes with lysosomes with consequences on the dynamics of retromer cycling on early endosomes, leading to the impaired sorting of Stx1 and Stx2 toxins from early endosomes to the Golgi network ( Selyunin et al., 2019 , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the role of ESCPE‐1 function in bacterial and viral infections is becoming clearer and could be of pivotal importance in uncovering novel pathways to target for innovative therapeutic approaches. For example, small molecules that inhibit SNX1‐dependent endosomal tubulation and retrograde trafficking of Shiga toxins were recently identified 152 . We hope that this work could encourage the exploration of ESCPE‐1 role in host–pathogen interaction and promote the identification of molecular interventions to target such interactions for reduced infection.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 90%
“…For example, small molecules that inhibit SNX1-dependent endosomal tubulation and retrograde trafficking of Shiga toxins were recently identified. 152 We hope that this work could encourage the exploration of ESCPE-1 role in host-pathogen interaction and promote the identification of molecular interventions to target such interactions for reduced infection.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 94%
“…Selyunin and colleagues have observed that the chemotherapeutic agent tamoxifen protects cells against Shiga toxins 1 and 2 by inhibiting their intracellular trafficking from early endosomes to the Golgi apparatus [3]. Initially, the authors thought that this effect was due to a modification of endosomal pH by tamoxifen.…”
mentioning
confidence: 99%